The Diversity of Cold Worlds: A Blended-light Binary Straddling the T/Y Transition in Brown Dwarfs - Daniella C. Bardalez Gagliuffi; Jacqueline K. Faherty; Genaro Suárez; Sherelyn Alejandro Merchan; Brianna Lacy; Ben Burningham; Klara Matuszewska; Rocio Kiman; Johanna M. Vos; Austin Rothermich; Jonathan Gagné; Caroline Morley; et al. (The Astrophysical Journal)
We present the first brown dwarf spectral binary characterized with JWST: WISE J014656.66+423410.0, the coldest blended-light brown dwarf binary straddling the T/Y transition. We obtained a moderate resolution ( R  ∼ 2700) G395H spectrum of this unresolved binary with JWST/NIRSpec and we fit it to late T and Y dwarf spectra from JWST/NIRSpec, and model spectra of comparable temperatures, both as individual spectra and pairs mimicking an unresolved binary system. We find that this tightly separated binary is likely composed of two unequal-brightness sources with a magnitude difference of 0.50 ± 0.08 mag in IRAC [4.5] and a secondary 1.01 ± 0.13 mag redder than the primary in [3.6]–[4.5]. Despite the large color difference between the best-fit primary and secondary, their temperature difference is only 92 ± 23 K, a feature reminiscing of the L/T transition. Carbon disequilibrium chemistry strongly shapes the mid-infrared spectra of these sources, as a complex function of the metallicity and surface gravity. While a larger library of JWST/NIRSpec spectra is needed to conclusively examine the peculiarities of blended-light sources, this spectral binary is a crucial pathfinder to both understand the spectral features of planetary-mass atmospheres and detect binarity in unresolved, moderate-resolution spectra of the coldest brown dwarfs.